2001
DOI: 10.1161/hq0901.095554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Clinical Presentation and Calcification of Culprit Coronary Artery Stenoses

Abstract: Abstract-Coronary artery calcification is increased in the presence of atherosclerosis. However, there is great variability in the calcification of individual coronary stenoses, and the clinical significance of this finding remains unknown. We tested the hypothesis that culprit lesions associated with myocardial infarction or unstable angina are less calcified than are stenoses associated with stable angina. The study consisted of 78 patients who underwent intravascular ultrasound imaging of culprit stenoses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(113 citation statements)
references
References 46 publications
(35 reference statements)
3
107
0
3
Order By: Relevance
“…Hence, one could hypothesize that small and spotty calcium deposits within an atherosclerotic plaque cause differences in tissue stiffness in the plaque, and the junction between the calcified and non-calcified tissues could act as a destabilizer, potentially leading to plaque rupture or fissuring. Indeed, recent clinical studies using IVUS and multislice CT (MSCT) have shown that coronary plaques with small spotty calcium deposits are more prone to rupture than severely calcified plaques [1][2][3]24) . It is conceivable, therefore, that discrete and spotty calcification, which contributes to differences in tissue tensile strength, together with other destabilizing factors such as endothelial dysfunction, plaque inflammation, and lipid accumulation, plays a role in the genesis of coronary plaque instability and the development of acute coronary events, which could cause high levels of plasma ox-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, one could hypothesize that small and spotty calcium deposits within an atherosclerotic plaque cause differences in tissue stiffness in the plaque, and the junction between the calcified and non-calcified tissues could act as a destabilizer, potentially leading to plaque rupture or fissuring. Indeed, recent clinical studies using IVUS and multislice CT (MSCT) have shown that coronary plaques with small spotty calcium deposits are more prone to rupture than severely calcified plaques [1][2][3]24) . It is conceivable, therefore, that discrete and spotty calcification, which contributes to differences in tissue tensile strength, together with other destabilizing factors such as endothelial dysfunction, plaque inflammation, and lipid accumulation, plays a role in the genesis of coronary plaque instability and the development of acute coronary events, which could cause high levels of plasma ox-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo studies, both IVMRI and IVUS showed high levels of agreement for identifying the presence and location of calcium, which is unsurprising, because IVUS excels at defining calcifications. 24 However, calcification interferes with measurement of atheroma size by IVUS, because outer vessel boundaries are lost because of acoustic shadowing; calcification poses no such difficulties in interpreting IVMRI. This problem was relatively frequent for IVUS, perhaps because iliac arteries tend to be calcified.…”
Section: Larose Et Al Ivmri For Plaque Characterizationmentioning
confidence: 99%
“…15,16 In contrast, established calcifications are seen as atherosclerotic end stage products and are associated with plaque stability. [17][18][19][20] It has been suggested that 18 F-NaF may additionally be a useful marker for plaque vulnerability. 21 Indeed, a clinical study by Joshi et al showed that ruptured and high-risk coronary plaques have a significantly higher 18 F-NaF uptake than non-culprit and low-risk coronary plaques.…”
Section: Introductionmentioning
confidence: 99%